A phytophagous braconid, Allorhogas conostegia sp nov (Hymenoptera: Braconidae), in the fruits of Conostegia xalapensis (Bonpl.) D. Don (Melastomataceae) - Chavarria, Laura [UNESP]; Hanson, Paul; Marsh, Paul; Shaw, Scott (Taylor & Francis Ltd, 2009)
Before 1989 all braconid wasps were thought to be parasitoids, but in that year the first phytophagous species was reported. Subsequently, a few other examples of phytophagy have been discovered, most of which are species of Allorhogas in the subfamily Doryctinae. Until now, all demonstrated examples of phytophagy in this genus have been as gall inducers in the fruits of Fabaceae. Here we describe a new species from Costa Rica, Allorhogas conostegia Marsh and Shaw, and provide evidence that it forms galls in the fruits of Conostegia xalapensis (Melastomataceae). We also provide information on the phenology of the plant and of the galls and the effects of the galls on the host plant, and we discuss the potential species richness of Allorhogas in the Neotropics.
Keywords: Doryctinae; galls; wasps